A objetividade natural espiritualizada em Ideen II de Husserl - Santos, Sanqueilo de Lima (2013)
The effort to go through the various forms of intentionality, in the constitution of objects of nature and spirit, is the goal for which they were produced in the complex descriptions Ideas II (1913 - 1922). The concept of regional ontology, which is treated Ideas I (1913) from the standpoint of its more general principles, is applied to particular problems in Ideen II, to demonstrate that reality and the characteristic features of each kind of objectivity (natural and spiritual) depend on intentionality. This is essential both to be donated, and to be recognized in its own ontological status. Our work focused on spiritual objectivity, and found himself thus engaged with themes that are present in the Cartesian Meditations (1931). The approach of spiritual objectivity depends on the exposure of the distinction between causality and motivation. Given the importance of the second, also requires more detailed analysis of the concepts of the spiritual world, empathy, intersubjectivity and expression. In the constitution of spiritual objectivity, its actually admits "predicates meaning" unlike natural objectivity. And our hypothesis is that the level of transcendental spirit, stated by Husserl, can only be sustained by a sense of ego, apparently secondary, whose predispositions of consciousness has essential debt with the body (Leib) and attitudes of parallelism